Pathogenicity of three strains of Metarhizium anisopliae on eggs and nymphs of Aeneolamia varia (Fabricius) (Hemiptera: Cercopidae) - ARANGO, GUILLERMO L.; TORRES, CELINA; LAPIONTE, STEPHEN L. (Revista Colombiana de Entomología, 1994)
The pathogenicity of three strains of the fungusMetarhizium anisopliae (Metch.) Sorokin was tested with eggs and nymphs of Aeneolamia varia (Fabricius). Eggs of A. varia that were sprayed with the fungus in Petri dishes with moist filter paper were unaffected by the three strains. The mean eclosion of treated eggs was 96.0 ± 3.2% compared with 98.0 ± 1.6% for the untreated control. To test the pathogenic effect against nymphs, the three strains were sprayed on the soil of pots planted with stems of Brachiaria ruziziensis infested with A. varia. The three strains were equally pathogenic toward the nymphs resulting in mean mortality of 46.1 ± 22.5% compared with 20.9 ± 13.4% for the check. There was a significant effect of the date of application on nymphal mortality. Nymphs reared in pots sprayed 8 days before egg eclosion suffered 58.5 ± 20.6% mortality. Nymphs reared in pots sprayed on the same day of the eclosion suffered 45.7 ± 14.5% mortality. Nymphs reared in pots sprayed 8 days after eclosion suffered 34.1 ± 24.6% mortality. Mortality in the untreated control was 20.9 ± 13.8%. This study indicates that M. anisopliae should be applied before the presence of the insect nymphs for more efficient control.